O direito penal negocial no âmbito da justiça militar da união: um estudo sobre o acordo de não persecução penal e os institutos despenalizadores com a índole do processo penal militar - Mello, Fernando Pessôa da Silveira (2024)
The thesis entitled "Negotiated Criminal Justice in the Scope of the Military Justice of the Union: A Study on the Non-Prosecution Agreement and the Diversionary Measures in Light of Military Criminal Procedure" analyzes the applicability of the Non- Prosecution Agreement within the Brazilian Federal Military Justice, considering the changes introduced by Law No. 13,491/2017 and Law No. 13,694/2019 (Anti-Crime Package). The study examines the evolution of Military Justice in Brazil, its normative and constitutional framework, as well as comparative experiences from other countries, highlighting the relationship between civil law and common law systems and the role of judicial precedents in ensuring legal certainty. The research delves into diversionary measures established in ordinary criminal legislation, such as plea bargaining, conditional suspension of prosecution, and, primarily, the NPA. It assesses their compatibility with the "nature of military criminal procedure," an indeterminate legal concept used by the Superior Military Court (STM) to justify the resistance to adopting these mechanisms within the Military Justice System. The thesis discusses case law from the STM, the Superior Court of Justice (STJ), and the Supreme Federal Court (STF), as well as the recent Incidental Resolution of Repetitive Demands (IRDR) decided by the STM, in which a majority ruled against the applicability of the NPA in military criminal proceedings. Grounded in legal consequentialism, the thesis explores the impacts of rejecting negotiated justice in the Military Justice context, analyzing its effects on equality between civilian and military defendants and the efficiency of judicial activity. The research concludes that the current prohibition on applying the NPA in the Military Justice System not only contravenes constitutional principles but also undermines the rationality and effectiveness of the criminal justice system. It suggests the need for a jurisprudential reinterpretation or legislative reform to align Military Justice with the advancements of contemporary criminal law..